Hubungan Self Awareness dengan Kadar Glukosa Darah pada Penderita Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Tuban - Rahma Fitri Choirunnisa; Lukman Hakim; Kusno Ferianto; Mei Widiawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Type 2 diabetes is a persistent medical condition with an increasing incidence that requires long-term treatment. One of the decisive factors in blood glucose control Patient self-awareness is a key variable examined in this study. The research was conducted to assess the relationship between self-awareness and blood glucose levels among individuals with type 2 diabetes in the Tuban Community Health Center area. A correlational analytic study with a cross-sectional design was utilized. The study involved a population of 135 patients, with a sample of 101 respondents selected using simple random sampling.Research data collection was conducted using a self-awareness questionnaire and a blood glucose observation sheet. Data analysis was performed using a chi-square test with a significance level of 0.05. The results of the analysis showed a p-value of 0.002 (p < 0.05), indicating a significant association between self-awareness and blood glucose levels. Based on these results, the study findings generally indicate that greater self-awareness typically allows for more optimal control of blood glucose levels.